2021
DOI: 10.1126/sciimmunol.abc7302
|View full text |Cite
|
Sign up to set email alerts
|

Human plasmacytoid dendritic cells mount a distinct antiviral response to virus-infected cells

Abstract: Plasmacytoid dendritic cells (pDCs) can rapidly produce interferons and other soluble factors in response to extracellular viruses or virus mimics such as CpG-containing DNA. pDCs can also recognize live cells infected with certain RNA viruses, but the relevance and functional consequences of such recognition remain unclear. We studied the response of primary DCs to the prototypical persistent DNA virus, human cytomegalovirus (CMV). Human pDCs produced high amounts of type I interferon (IFN-I) when incubated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…These results were later recapitulated using SARS-CoV-2 as the stimulus ( 25 ). Using mass cytometry, it was further shown that human pDCs mount distinct, heterogenous responses dependent on the stimulus ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results were later recapitulated using SARS-CoV-2 as the stimulus ( 25 ). Using mass cytometry, it was further shown that human pDCs mount distinct, heterogenous responses dependent on the stimulus ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, individual viral particles can vary in their replication efficiency inside the host, leading to differences in host cell signaling and subsequent IFN-I secretion [22,32]. Finally, a recent report showed that the recognition of live cytomegalovirus-infected cells mounted different IFN-I response dynamics in vitro in human primary plasmacytoid dendritic cells (pDCs) compared with the self-recognition of virus mimetics [33].…”
Section: Glossarymentioning
confidence: 99%
“…These results were later recapitulated using SARS-CoV-2 as the stimulus (Onodi et al, 2021). Using mass cytometry, it was further shown that human pDCs mount distinct, heterogenous responses dependent on the stimulus (Yun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%